Effect of mixed water and methanol solvents ratio on the CaCO3 characteristics via fine bubble diffuser as a dental biomaterial - Febrida, Renny; Ramadhan, Muhammad Farhan; Karlina, Elin; Andiesta, Niekla Survia (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: The application of calcium carbonate in dental biomaterial depends on the charcateristics after the synthesis process. This study aims to determine the effect of the ratio of methanol and water on the characteristics of the CaCo3 produced through the fine bubble diffuser method. Methods: Synthesis of calcium carbonate by CO2 carbonation method using fine bubble diffuser to produce fine CO2 bubbles (bubble size range 100-500 nm). The Ca(OH)2 precursor was dissolved in various ratios of water and methanol mixtures, namely: 25% water 75% methanol, 20% water 80% methanol, 15% water 85% methanol, 10% water 90% methanol, 5% water 95% methanol, and 100% methanol. The suspension was carbonated using CO2 fine bubbles for 2 hours to produce CaCO3 powder. The resulting calcium carbonate powder was tested with FTIR (Fourier Transform Infra Red), PSA (Particle Size Analyzer), and Zeta-Potential. Results: The FTIR test obtained the wave numbers of calcite (712 cm-1), vaterite (744, 873, 874, and 875 cm-1) and aragonite (848, 849, and 854 cm-1) phases in the six variations of the solvent used. The PSA test showed that the particle size produced was submicron with the smallest size being 191.1 nm and the largest being 576.2 nm. The ZetaPotential test showed that the particles were relatively stable in solution with a Zeta-Potential value range of -15.1 mV to -20.8 mV and particles with moderate stability -21.2 mV to -25.1 mV. Conclusion: The addition of the organic solvent methanol to water increases the solubility of CaOH and increases the formation of the vaterite phase. Increasing the amount of water decreases the amount of vaterite phase, increasing the particle size and zeta potential value. but the addition of 15% water decreases the particle size of CaCO3 KEY WORDSCaCO3, fine bubble diffuser, FTIR, PSA, zeta potential Pengaruh perbandingan campuran pelarut air dan metanol terhadap karakteristik CaCO3 melalui metode fine bubble diffuser sebagai biomaterial kedokteran gigiABSTRAKPendahuluan: Kalsium karbonat (CaCO3) merupakan salah satu sumber kalsium yang umum digunakan di bidang biomaterial kedokteran gigi. Aplikasi kalsium karbonat tergantung dari fasa dan ukuran partikelnya. Penelitian ini bertujuan untuk mengetahui pengaruh perbandingan metanol dan air terhadap karakteristik CaCO3 yang dihasilkan melalui metode fine bubble diffuser. Metode: Prekursor Ca(OH)2 dilarutkan dengan berbagai variasi campuran pelarut air dan metanol, yaitu: 25% air 75% metanol, 20% air 80% metanol, 15% air 85% metanol, 10% air 90% metanol, 5% air 95% metanol, dan 100% metanol. Suspensi Ca(OH)2 dikarbonasi menggunakan gelembung halus CO2 selama 2 jam untuk menghasilkan bubuk CaCO3. Bubuk CaCO3 yang dihasilkan diuji dengan FTIR (Fourier Transform Infra Red), PSA (Particle Size Analyzer), dan ZetaPotential. Hasil: Uji FTIR didapatkan bilangan gelombang fasa kalsit (712 cm-1 ), vaterit (744, 873, 874, dan 875 cm-1 ) dan aragonit (848, 849, dan 854 cm-1 ) pada keenam variasi pelarut yang digunakan. Uji PSA didapatkan ukuran partikel terkecil 191,1 nm dan terbesar 576,2 nm. Partikel relatif stabil dalam larutan berdasarkan Uji Zeta-Potential (-15,1 mV sampai -17,8 mV) dan stabilitas moderat (-20,8 mV sampai -25,1 mV). Simpulan: Penambahan pelarut organik methanol pada pelarut air meningkatkan kelarutan CaOH dan meningkatkan pembentukan fasa vaterite. peningkatan jumlah air menurunkan jumlah fasa vaterite, meningkatkan ukuran partikel dan nilai zeta potensial. namun pada penambahan 15% air dan seterusnya menurunkan ukuran partikel CaCO3. KATA KUNCI CaCO3, fine bubble diffuser, FTIR, PSA, zeta potential